Metabolomic profiles of Ribes nigrum L. and Lonicera caerulea L. from the collection of the N.I. Vavilov Institute in the setting of Northwest Russia - T. V. Shelenga; V. S. Popov; A. V. Konarev; N. G. Tikhonova; O. A. Tikhonova; Y. A. Kerv; A. E. Smolenskaya; L. L. Malyshev (Вавиловский журнал генетики и селекции)
Recently, the trend of using fruit and berry crops as ingredients for functional and dietary nutrition, the development and implementation of flavors, pigments, new medicines and dietary supplements has been actualized. Because the direction of use depends on the biochemical properties of fruits, which are determined not only by species and varietal characteristics, but also by reproduction conditions, the study of the biochemical composition of fruits grown in various regions of the world continues to be relevant. In this regard, the collection of N.I. Vavilov Institute (VIR), which has a wide diversity of fruit and berry crops, is of great interest for study. Ribes nigrum fruits have a balanced set of sugars, organic acids, essential oils, microelements, a high content of vitamins, anthocyanins, pectins. Lonicera caerulea fruits are characterized by high values of phenolic substances: bioflavonoids, hydroxycinnamic acids, flavonols, polyphenols, anthocyanins, as well as vitamins, carotenoids, iridoid glycosides and other natural antioxidants. The investigation of L. caerulea and R. nigrum fruit’s accessions from the VIR collection using gas-liquid chromatography with mass spectrometry allows us to obtain new information about the biochemical characteristics of fruits, to identify L. caerulea and R. nigrum varieties with optimal economically valuable characteristics, to determine the specificity of L. caerulea and R. nigrum metabolomic spectra in the setting of Northwest Russia. As a result of the analysis, typical compounds of the metabolomic profile of each culture were identified. Organic acids, phenol-containing compounds and polyols prevailed in L. caerulea, while mono- and oligosaccharides, in R. nigrum. The qualitative composition of the black currant varieties ‘Malen’kii Printz’, ‘Dobriyi Dzhinn’, ‘Tisel’, ‘Orlovskii Val’s’, and blue honeysuckle ‘S 322-4’, ‘Malvina’, ‘Leningradsky Velikan’ was optimal for food consumption; the varieties of blue honeysuckle ‘Bazhovskaya’ and black currant ‘Aleander’ had a good representation of biologically active compounds, which makes samples attractive as raw materials for the production of biologically active additives, including with the use of microorganisms’ cultures.